D6.3 Workplan for transfer of knowledge and experience (update 2) - Hadjimitsis, Diofantos G.; Scheirer, Gunter; Krauss, Thomas; Kontoes, Haris; Kaskara, Mariza; Bühl, Johannes; Seifert, Patric; Kazadzis, Stelios; Pittaki-Chrysodonta, Zampela; Themistocleous, Kyriacos (My University, 2023)
Deliverable D.6.3 ‘Workplan for transfer of knowledge and experience’ focuses on the activities carried out for the transfer of knowledge and experience during the Capacity Building Scheme period 'A' (M26 to M44), and the workplan for knowledge transfer and experience during the upcoming Capacity Building Scheme B. Various activities such as workshops, trainings, seminars, and webinars were implemented by the Strategic Partners to facilitate capacity building and knowledge transfer to the ERATOSTHENES CoE researchers. Additionally, an initial plan for Capacity Building Scheme B is provided, which was designed in collaboration with the Strategic Partners of the EXCELSIOR project (TROPOS, DLR, NOA, and PMOD/WRC).
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation